INFLUENCE OF CALCIUM DOSES AND SEED QUALITY ON THE YIELD OFPOTATO (Solanum tuberosum L.) - Coaquira Incacari , Roberto (2025)
Nutritional mismanagement and the use of low-quality seed tubers significantly limit the yield and quality of potato crops. The purpose of the present study was to evaluate the effect of different calcium (Ca) doses on the agronomic performance of the potato crop, Canchan cultivar, using farmer or conventional seed tubers (declared category) and certified category seed tubers. The study was conducted at the San Juan de Yanamuclo farm, in San Lorenzo District, Jauja Province, Junín, using a randomized completely block design in divided plots with four replications. Seed types (conventional and certified category) the subplot level the Ca doses (0, 30, 60, 90, 120, 150, and 180 Kg·ha-1) were distributed. The results show that the application of 180 Kg·ha-1 of Ca, regardless of the seed type used, increased the tuber weight per plant and per area in the Canchan cultivar, as well as the number of stems, tubers, and their length. Additionally, the highest weights of first-category tubers were obtained with 120 and 180 Kg·ha-1 of Ca using certified and conventional seed, respectively. Likewise, higher weights of second- and third-category tubers were observed with the application of 180 Kg·ha-1 of Ca, with no differences between the evaluated seed types.